ANALISIS MAKNA KONTEKSTUAL AL-NUR DALAM AL-QUR’AN: KAJIAN TAFSIR TEMATIK - Rohman, Abdul (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
In the Qur'an, there are three types of words: (1) words that have only one meaning; (2) words that contain other meanings; (3) words whose meanings require further explanation. One term in the Qur'an that is interesting to study due to its derivative meanings is al-nur, which contains additional meanings and still requires further clarification. This article aims to examine and analyze the contextual meanings of the term al-nur in the Qur'an. This research is a library research, and the method used is descriptive-analytical, with a thematic tafsir approach. After thematically studying and collecting verses that mention al-nur, the researcher finds that al-nur in the Qur'an has derivative meanings, including the Essence of Allah, Islam, faith, the Qur'an and other books of Allah, the light given by Allah to the believers in the Hereafter, and the light of the sun and moon. Specifically, the meaning of al-nur encompasses both material and spiritual aspects. In conclusion, the derivative meanings of al-nur depend on the context of the verse and the narratives that explain its meaning. However, despite the differences in the meanings of al-nur in the Qur'an, they are still interconnected. If arranged in order, it is understood that the source of all light is the Essence of Allah, which manifests as light, and this light illuminates the heavens and the earth, whether in a spiritual or material form.